3D radar wavefield tomography of comet interiors. Issue 8 (15th April 2018) - Sava, Paul; Asphaug, Erik
Abstract: Answering fundamental questions about the origin and evolution of small planetary bodies hinges on our ability to image their surface and interior structure in detail and at high resolution. The interior structure is not easily accessible without systematic imaging using, e.g., radar transmission and reflection data from multiple viewpoints, as in medical tomography. Radar tomography can be performed using methodology adapted from terrestrial exploration seismology. Our feasibility study primarily focuses on full wavefield methods that facilitate high quality imaging of small body interiors. We consider the case of a monostatic system (co-located transmitters and receivers) operated in various frequency bands between 5 and 15 MHz, from a spacecraft in slow polar orbit around a spinning comet nucleus. Using realistic numerical experiments, we demonstrate that wavefield techniques can generate high resolution tomograms of comets nuclei with arbitrary shape and complex interior properties.